Clinical efficacy of exercise in the treatment of post-COVID-19 syndrome: a systematic review and network meta-analysis - Du, Shaojie; Cui, Zeyu; Xu, Xiangqian; Liu, Te; Ye, Jie (Frontiers in Physiology, 2025)
BackgroundPost-COVID-19 syndrome (PCS) describes a constellation of persistent or new symptoms lasting beyond the acute phase of SARS-CoV-2 infection. Emerging evidence suggests that exercise is a cost-effective and accessible intervention that may enhance pulmonary function, improve cardiopulmonary circulation, regulate emotional status, and alleviate symptoms of PCS. However, robust evidence supporting the efficacy of exercise therapy in PCS remains limited. This systematic review and meta-analysis aimed to elucidate the therapeutic potential of exercise therapy in PCS.MethodA search of the PubMed, Embase, Web of Science, and Ovid databases up to March 25, 2025 yielded 33 randomized controlled trials (with 2,895 participants) for meta-analysis.ResultThe results showed that exercise therapy significantly improved the multi-dimensional outcomes of patients with PCS. Bayesian network meta-analysis indicated that the combination of aerobic exercise and respiratory muscle training had the best effect on lung function. Multimodal exercise significantly improved the results of the six-minute walk test, the dyspnea score, and peak oxygen uptake. Mental Health and Mental Component Summary scores improved significantly in the group that received exercise therapy (P<0.01).ConclusionThe results of this meta-analysis confirm that exercise can significantly improve quality of life and the emotional state of patients with PCS. They also provide evidence for a treatment strategy in patients with post-COVID-19 sequelae.Systematic Review registrationhttps://www.crd.york.ac.uk/PROSPERO/#myprospero, identifier CRD420251034187.